Self-efficacy, organizational commitment, workload as predictors of life satisfaction in elementary school teachers: the mediating role of job satisfaction - Cayupe, Juan C.; Bernedo-Moreira, David Hugo; Morales-García, Wilter C.; Alcaraz, Fátima López; Peña, Karla Berenice Carrazco; Saintila, Jacksaint; Flores-Paredes, Alcides (Frontiers in Psychology, 2023)
Background: Life satisfaction as well as job satisfaction of teachers has a significant impact on educational outcomes. Objective: To evaluate a model of factors predicting life satisfaction through the mediating role of job satisfaction. Methods: This was a cross-sectional study, with a sample of 300 primary school teachers of both sexes (68% female, 32% male) and with a mean age of 42.52 years (SD=10.04). They were administered the General Self-Efficacy Scale, the Satisfaction with Life Scale (SWLS), the Workload Scale (ECT), the Generic Job Satisfaction Scale, and the Organizational Commitment Questionnaire (OCQ). Structural equation modeling (SEM) was used for data analysis. Results: The SEM analysis found significant goodness-of-fit indices: χ2 = 13.739; df = 5; p = <.001; CFI = 0.99, TLI = 0.98, RMSEA = 0.05, SRMR = 0.04). Specifically, self-efficacy and organizational commitment were positive predictors of job satisfaction, while workload was a negative predictor of job satisfaction. The mediating effect of job satisfaction between self-efficacy, life satisfaction, workload, and overall life satisfaction was confirmed. Conclusion: The results confirm the importance of self-efficacy, organizational commitment, and workload in job satisfaction and overall life satisfaction of elementary education teachers. Job satisfaction acts as a mediator in this relationship. It is important to reduce workload and promote self-efficacy and organizational commitment to improve the well-being and satisfaction of teachers.